PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS V UPT SD NEGERI 060937 MEDAN JOHOR - Br Sitepu, Harty Erima; Regina Sipayung; Irmina Pinem; Darinda Sofia Tanjung; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Team Games Tournament type cooperative learning model on improving student learning outcomes in the subject of IPAS with the material of national cultural diversity in the 5th grade of UPT SD Negeri 060937 Medan Johor, Academic Year 2024/2025. The independent variable in this study is the Team Games Tournament type cooperative learning model (X) and the dependent variable is Student Learning Outcomes (Y). In this study, the research method used is quantitative and the research design is a Pre-Experiment specifically One Group Pretest Posttest Design. The sample for this research consists of 30 students from the 5th grade of UPT SD Negeri 060937 Medan Johor. The sampling method used in this research is Total Sampling. The research instrument consisted of a questionnaire and a multiple-choice test instrument. The learning outcomes of the students showed an average pretest score of 57.33 while the average posttest score was 82.80, and for the student questionnaire, the average score was 78.43. The level of success in student learning outcomes increased as evidenced by the correlation test result of 0.432, which means rcount ≥ rtabel, namely 0.432 ≥ 0.361. Furthermore, the hypothesis test (t-test) shows that tcount ≥ ttabel, namely 2.537 ≥ 1.697, Therefore, it can be stated that Ha is accepted. This indicates that there is a significant positive influence from the cooperative learning model of the Team Games Tournament type on learning outcomes in the subject of IPAS in class V UPT SD Negeri 060937 Medan Johor for the 2024/2025 academic year.